Plan para el mantenimiento de equipos biomédicos del Hospital Universitario Motupe. - Ochoa Armijos, Grace Estefania (2015)
Health centers currently acquire the latest electronic technology in medical equipment. In order to achieve success in treatment, diagnosis and rehabilitation of diseases, they depend entirely on the technology they use. This thesis project consists in developing a maintenance plan for the biomedical equipment used in the areas of Paediatric Dentistry, clinical laboratories, ecosonography and operating rooms of the Motupe University Hospital, based on the specifications of each equipment’s manufacturer regarding functioning and standards in order that they are in proper operating condition, ensuring their reliability, electrical safety, reduced downtime, which will increase productivity and quality of service. The preventive maintenance has been structured as follows: development of resumes, writing maintenance routine and formats. Once a comparative analysis of some commercially available software was applied, the right software for maintenance was determined in hopes that in future would be implemented.